ON THE NEGATIVE CONSEQUENCES OF CLIMATE CHANGE IN THE 21ST CENTURY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
At present, the most vulnerable part of nature and society has become the process of climate change at the present stage. The article considers the problems of global warming in the context of air pollution, taking into account the development of scientific and technological progress. An analysis of the causes of climate change in general throughout the world and its negative consequences in the modern world is given. The article also considers the factors influencing the process of climate change, and gives recommendations for eliminating the negative consequences due to climate change.